Abundance, patterns, and taxa associations of anthropogenic marine debris on reefs in the middle Florida Keys - Payton, Tokea G.; Sims, Randi J.; Childress, Michael J. (Frontiers in Marine Science, 2024)
The Florida Keys reef tract has rapidly shifted from a structurally complex, hard coral-dominated reef to a less rugose, soft coral-dominated reef. This transition has been facilitated by persistent anthropogenic stressors including recreational and commercial fishing and increased anthropogenic marine debris. During the summers of 2020–2022, benthic censuses were conducted to identify substrate and marine debris composition for 30 reefs in the middle Florida Keys. Inshore reefs contained higher rugosity, coral cover, and marine debris abundance primarily comprised of monofilament and rope from fishing traps. Plastic items (e.g., ropes and monofilament) overall had the highest species diversity. Additionally, marine debris appears to promote turf algae growth on inshore reefs. While is it not yet possible to determine if this pattern of high debris nearshore is due to proximity to onshore debris sources, accumulation due to higher rugosity snagging debris, or increased debris removal efforts offshore, these differences in marine debris types and abundances suggest variability in potential impacts of debris on marine biota on inshore versus offshore reefs. Therefore, the differential use of marine debris by associated biota should be considered in marine debris management practices.